Analysis of the Effect of the Hydraulic Press Method on the Yield and Characteristics of Essential Oils from Various Varieties of Citrus Peel - Dewi Arziyah; Sri Mutiar; Islahuddin Islahuddin; Nurul Aini (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aims to determine the yield and characteristics of essential oil extracted from orange peel. Currently, citrus peel extraction is typically performed using solvents and high temperatures, which can affect oil yield and quality. In this study, a mechanical extraction method driven by hydraulic power without heating was employed, with the aim of increasing yield while optimizing the essential oil’s composition, particularly the content of bicyclic compounds and carenes compared to conventional limonene-based methods. The utilization of citrus peels, which have traditionally been treated as waste, holds significant potential for processing into value-added products, one of which is essential oil. The materials used were Sundai  peels, lemon peels, sweet orange peels, kaffir lime peels, and kasturi  peels. The results of the study indicate that sundai orange peel is more optimal compared to other varieties because it has an peel composition of 34.2125 ± 0.20%, a moisture content of 64.482 ± 0.75%, a yield of 0.779 ± 0.03%, and a density of 0.8387 ± 0.003 g/ml. Based on the chromatogram data, at least 10 major peaks with different retention times were detected, representing the components of the essential oil. The identified compounds include 3-Carene, (+)-Carene, ?-Terpinene, Octanal, bicyclic compounds (bicyclo[3.1.1]heptane and its derivatives), and Nonyl chloroformate (a minor component). Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land